2016
DOI: 10.1155/2016/7675953
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis Influencing Postoperative Hospital Stay and Medical Costs for Patients with Definite, Suspected, or Unmatched Diagnosis of Acute Cholecystitis according to the Tokyo Guidelines 2013

Abstract: Purpose. To identify significant independent preoperative factors influencing postoperative hospital stay (PHS) and medical costs (MC) in 171 patients who underwent cholecystectomy for benign gallbladder diseases and had definite, suspected, or unmatched acute cholecystitis (AC) diagnosis according to the Tokyo Guidelines 2013 (TG13). Methods. The 171 patients were classified according to the combination of diagnostic criteria including local signs of inflammation (A), systemic signs of inflammation (B), and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…Grade I (mild) comprises cases other than Grades II and III, with lower risk of death and surgical risk that can easily be treated by laparoscopic cholecystectomy (LC). Since the Tokyo Guidelines (TG) have become widely known worldwide, recent multidirectional studies have evaluated the TG13 severity grading criteria for AC . In Tunisia, the spread of the TG has increased the rate of LC, significantly reducing preoperative and total hospital stay without increasing intra‐ and postoperative complications ; in Taiwan, Cheng et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grade I (mild) comprises cases other than Grades II and III, with lower risk of death and surgical risk that can easily be treated by laparoscopic cholecystectomy (LC). Since the Tokyo Guidelines (TG) have become widely known worldwide, recent multidirectional studies have evaluated the TG13 severity grading criteria for AC . In Tunisia, the spread of the TG has increased the rate of LC, significantly reducing preoperative and total hospital stay without increasing intra‐ and postoperative complications ; in Taiwan, Cheng et al.…”
Section: Introductionmentioning
confidence: 99%
“…In Tunisia, the spread of the TG has increased the rate of LC, significantly reducing preoperative and total hospital stay without increasing intra‐ and postoperative complications ; in Taiwan, Cheng et al. mentioned the complication rate and the length of hospital stay increased along with the severity grade of the TG ; and in Japan, too, a significant correlation has been reported between severity grade and both prolonged postoperative hospital stay and medical cost . Wright et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TG13 severity grading is thus well regarded as a factor predicting vital prognosis. Studies have also found that the length of hospital stay increases significantly for patients at higher grades according to the TG13 severity grading (Table ).…”
Section: Introductionmentioning
confidence: 98%
“…The TG13 diagnostic criteria for acute cholecystitis constitute exactly this combination, and we considered that they share the same concept for the designation of diagnostic criteria. A Japanese study of the association between diagnostic criteria and factors such as length of hospitalization and medical costs found statistically significant differences between definitive and suspected diagnoses , demonstrating the effectiveness of these diagnostic criteria. In light of the results of such validation studies, we considered that there are no major problems with the TG13 diagnostic criteria for acute cholecystitis, and recommend that they be used unchanged as the TG18/TG13 diagnostic criteria (Table ).…”
Section: Introductionmentioning
confidence: 99%